A successful model for socio-economic upliftment of tribal farmers of Chhattisgarh - Mooventhan, P; Dixit, Anil; Khan, M A; Sharma, G L; Verma, L K; Verma, Praveen; Venkatesan, P; Singh, SRK; Singh, Uttam; Ghosh, P K (Indian Farming, 2022)
Farmer FIRST programme was implemented with an aim to improve the tribal farmer's livelihood and socio-economic status through promising agricultural enterprises integration in rice fallow. Based on 6 years of experience on the Farmer FIRST, it was learnt thatthe group approach is highly suitable under resourcepoor conditions, small-scale technologies are more suitable to generate additional income of tribal farmers, involvement of local/farmers resources creates more involvement of farmers in the project activities and low-cost technologies are having more acceptance and adoption rate. With these lessons, we can upscale this FFP model by promoting rural entrepreneurship to sustain the farm income, scaling-up of the small-scale agro-processing units to reduce the seasonal migration of the farmers, increased capital accumulation with lowcost innovations to empower the small and marginalfarmers in the resource-poor rural sett ings. Particularly, the rural development projects should combine with infrastructure development, education, investment in agriculture and the promotion of rural non-farm activities where rural women and youths can engage themselves.